2020
DOI: 10.3390/f11010100
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Forest Areas in Myanmar Based on Socioeconomic Factors

Abstract: National circumstances should be considered in establishing and adjusting forest reference emission levels (FRELs/FRLs) under the United Nations Programme on Reducing Emissions from Deforestation and Forest Degradation (UN-REDD+ Programme). Myanmar, one of the world's least developed countries may face accelerating deforestation under an open and democratic political system that desires rapid economic development. This research analyzes the impacts of population growth and economic development on forest areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Intuitively, we would expect the opposite: an inverse relationship between socioeconomic development and environmental impact. However, it has been reported that deforestation rates increase with the rise of socioeconomic indicators (Michinaka et al 2020). In this sense, it is argued that the relationship between socioeconomic indicators and environmental issues behaves like a Kuznets curve (Stern 2004), where there is an initial phase where the relationship is positive, as we have detected, and in a second phase it becomes negative (Cropper et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Intuitively, we would expect the opposite: an inverse relationship between socioeconomic development and environmental impact. However, it has been reported that deforestation rates increase with the rise of socioeconomic indicators (Michinaka et al 2020). In this sense, it is argued that the relationship between socioeconomic indicators and environmental issues behaves like a Kuznets curve (Stern 2004), where there is an initial phase where the relationship is positive, as we have detected, and in a second phase it becomes negative (Cropper et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Based on environmental variables, it is projected that in a world that is 2.0 °C hotter, by 2100 or sooner, bat hosts of sarbecoviruses may shift to Myanmar, Laos, Vietnam, Cambodia and India, countries that account for the highest number of suitable hosts (Muylaert et al, 2022). In some of these countries, population growth and economic development have resulted in greater deforestation (Michinaka et al, 2020) and land use changes, whereas among the remaining wild life, the prevalence of coronavirus increases directly because of human impact (Warmuth et al, 2023).…”
Section: A Warming World In Displacementmentioning
confidence: 99%
“…However, Soe and Yeo-Chaung (2019) pointed out that the production of natural forest cannot fulfill the demand of the local people, therefore, the consequent of overexploitation is affecting million hectares of natural forest in Myanmar. And deforestation rate is also expected to increase as the human population and economy grow (Michinaka et al 2020). Studies of NTFPs in Myanmar have focused on the income that rural communities derive from NTFP production and trade but research examining the ecological impacts of NTFP production are fewer by comparison.…”
Section: Introductionmentioning
confidence: 99%